Optimal scheduling for charging and discharging of electric vehicles - Lin, Shen (Nanyang Technological University, 2021)
With the development of the times, people gradually realize that oil and other non-renewable energy sources are increasingly exhausted. Under the background of increasing energy shortage, the traditional gasoline driven vehicles will be eliminated in the future. With the breakthrough of key technologies of electric vehicles and the popularization of low-carbon concept, electric vehicles, as a fast-growing new energy vehicle, have been strongly supported by the government. With the popularity of electric vehicles, new problems gradually arise. A large number of electric vehicles have problems such as non-standard charging time and voltage requirements, which have brought great harm to the whole power transmission system. It can also increase the operation cost and harmonic pollution. As a distributed energy storage unit, electric vehicles can not only cut the peak load and fill the valley load for the power grid but also bring benefits to electric vehicle users when they supply power to the power grid in the reverse direction. In order to achieve this goal, a reasonable optimal scheduling scheme is needed.